STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH DARI SEKTOR PAJAK HOTEL DAN RESTORAN DI KABUPATEN JEMBER - Kahar Haerah (Universitas Muhammadiyah Jember, 2017)
From the results of research conducted shows that the small tax revenue from the tax sector of hotels and restaurants caused by several factors including: still lack of counseling or socialization to the taxpayers; lack of taxpayer awareness; lack of administrative efficiency and high cost of collection.To improve the local tax revenues, especially from the hotel and restaurant tax sector, the choice of strategy that can be done by Jembber regency government are: (a) to optimize Hotel Tax and Restaurant Tax Intensification and Taxation Program; (b) performing hotel taxpayer checks and restaurant taxes effectively; (c) maximizing the utilization of the network of tax information service system; (d) increasing extension to taxpayers; (e) increasing the taxpayer's human resources and the local tax apparatus; (f) improve administrative efficiency and reduce collection costs; (g) enhance cooperation with businesses and communities by preparing all the facilities of hotels and restaurants more attractive; (h) grow regional economy, increase foreign exchange, and provide job opportunities that can improve the welfare of the wider community; (i) enhance cooperation and coordination with hotel and restaurant entrepreneurs and other concerned parties to co-manage and maintain security and order; (j) improve coordination Among all tax apparatus; (k) the application of online taxes; and (l) to intensively socialize hotel tax and restaurant tax policies.Keywords: Strategy, Local Original Income, Hotel and Restaurant Tax